Imaging in Patients With Visual Symptoms. Issue 5 (October 2016) - Szatmáry, Gabriella
Abstract : ABSTRACT: Purpose of Review: This article presents an imaging-based approach to the differential diagnosis of visual symptoms. Recent Findings: Many neurologic disorders may present with visual symptoms. Therefore, neurologists must be familiar with the array of pathophysiologic processes that cause visual symptoms. Orbital imaging is challenging owing to the small structures and different tissue interfaces within and surrounding the orbital compartment. Some of the emerging three-dimensional MRI sequences are promising and compare well with high-resolution two-dimensional sequences in the orbits. Summary: The diagnosis of patients with visual symptoms can be challenging and often requires in-depth knowledge of neuroanatomy that is well depicted by various imaging methods. Neurologists are expected to be familiar with the latest imaging techniques that play an important role not only in diagnosing diseases but also in determining disease pathogenesis. Close collaboration with the neuroimager, ophthalmologist, and, when available, neuro-ophthalmologist, is recommended when caring for patients with visual symptoms.